Estimation of the Domestic Agricultural Sector Potential for the Growth of Energy Cultures for Bioenergy Fuel Production (Agricultural Engineering, 2021)
The article presents discussion on the state and prospects of bioenergy development in the context of rationalization of energy crops application as resource potential of Ukraine. Along with the development of society and increase of life intensity, the needs of mankind with regard to energy resources are increasing. The reduction rates of traditional types of energy resources are progressively growing, and their shortage is increasing. In addition, Ukraine belongs to import-dependent countries in the energy sector. At the expense of its own sources, our country provides only about half of the energy needs, while domestic national economy is one of the most energy-intensive industries in the world. In this regard, there is an urgent need to search for new, alternative sources of energy. Taking into account the potential present in Ukraine, the biomass use for energy production is the most attractive option. However, along with this, there is a problem of purposeful use of the agricultural land and a competitive struggle between agricultural products for nutrition and energy purposes. At the same time, many problems arise, which concerdevelopment of an appropriate legislative framework, methodological approaches to the economic, environmental and social efficiency of production and use of biological types of energy.